1975
DOI: 10.1111/j.1749-6632.1975.tb19234.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of Microtubules in the Phasic Pattern of Insulin Release*

Abstract: The release of insulin evoked by glucose and other insulinotropic agents in the pancreatic B-cell represents the outcome of a sequence of cellular events including the recognition of the secretagogue, the subsequent modification of cationic fluxes, and the eventual extrusion of secretory granules into the extracellular space.l Investigations on 45calcium net uptake, subcellular distribution, and efflux in isolated islets have led to the concept that, whatever the stimulatory agent used, the secretory response … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
56
0
1

Year Published

1976
1976
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(58 citation statements)
references
References 47 publications
(8 reference statements)
1
56
0
1
Order By: Relevance
“…In designing this experiment, we took into account the time-and dose-related effect of mitotic spindleinhibitors upon the B-cell microtubular apparatus (23), so that the labeling of the islets occurred at a time (Table I). It fell slightly during the second incubation (120th-210th min) to 79.4+7.4% of its initial paired value.…”
Section: Resultsmentioning
confidence: 99%
“…In designing this experiment, we took into account the time-and dose-related effect of mitotic spindleinhibitors upon the B-cell microtubular apparatus (23), so that the labeling of the islets occurred at a time (Table I). It fell slightly during the second incubation (120th-210th min) to 79.4+7.4% of its initial paired value.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that colchicine blocks the cyclooxygenase-2 (COX-2) activity, prostaglandin E 2 and thromboxane A 2 synthesis of mononuclear phagocytes with subsequent reduction of swelling and pain in gout and Familial Mediterranean Fever (FMF) (Pouliot et al, 1998). In addition, this colchicine is known for tyrosine phosphorylation and superoxide anion production inhibitor (Roberge et al, 1996), arachidonate release and 5-lipoxygenase inhibition (Peters-Golden et al, 1996;Zurier et al, 1973), histamine inhibition (Mekori et al, 1989), insulin and parathomone release (Gillespie et al, 1968;Malaisse et al, 1975). Colchicine at high dose causes bone marrow failure, skin eruption, nettle rash, stomatitis and intestinal bleeding.…”
Section: Introductionmentioning
confidence: 99%
“…3 " 5 We have also shown that vincristine and colchicine inhibit glucose-induced insulin release in vivo. 6 - 7 However, our recent studies 8 - 9 have shown that in the intact rat: (1) vincristine caused inhibition of glucose-induced insulin release in the presence or absence of morphologic disruption of the beta-cell microtubules; but, in contrast, (2) vincristine failed to inhibit arginine-induced insulin release either in the presence or absence of the beta-cell microtubular disruption.…”
mentioning
confidence: 83%